Advancing Perspectives on Consumer Behavior in Healthy Food Consumption within Modern Digital and Social Environments - Febri Siahaan; Amanda Sona Priscillia (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2026)
Background: Despite increasing exposure to health-related information in digital environments, many consumers still do not consistently translate health awareness into healthy food purchasing behavior, reflecting a persistent attitude–behavior gap. Purpose: This study examines how digital and perceptual factors shape healthy food purchase behavior through consumers’ internal psychological processes. Method: A quantitative cross-sectional approach was used, involving 300 respondents from Tangerang Raya, Indonesia. The data were analyzed using PLS-SEM to examine the proposed relationships among the variables. Findings: The findings show that digital marketing quality, influencer credibility, brand authenticity, and perceived ethical value significantly contribute to health consciousness, with influencer credibility emerging as the strongest predictor. Health consciousness significantly influences healthy food purchase behavior and serves as an important mechanism linking external stimuli with consumer responses. Furthermore, food neophobia does not significantly moderate this relationship, suggesting that health-oriented consumers tend to maintain healthy purchasing behavior regardless of their reluctance toward unfamiliar foods. Conclusions: These findings provide a deeper understanding of how consumers process digital information and translate it into healthy food purchasing behavior through internal psychological mechanisms. Research implication: This study extends the Stimulus-Organism-Response framework by integrating digital marketing and value-based perceptions within a single model while highlighting the central role of health consciousness in healthy food purchase decisions.